Challenges in Implementation of the ANISA Protocol at the Odisha Site in India. Issue 5 (May 2016) - Satpathy, Radhanath; Nanda, Pritish; Nanda, Nimai C.; Bal, Himadri B.; Mohanty, Ranjita; Mishra, Archana; Swain, Tapoja; Pradhan, Keshab C.; Panigrahi, Kalpana; Dutta, Ambarish; Misra, Pravas R.; Parida, Sailajanandan; et al.
Abstract : Background: The Aetiology of Neonatal Infection in South Asia (ANISA) study is being carried out at 5 sites across Bangladesh, India and Pakistan, generating in-depth information on etiologic agents in the community setting. Pregnancies are identified, births are registered and young infants are followed up to 59 days old with regular assessments for possible serious bacterial infection following a generic protocol. Specimens are collected from suspected cases. This article describes the challenges in implementing the generic ANISA protocol and modifications made to accommodate the Odisha site, India. Challenges: Primary challenges in implementing the protocol are the large geographic area, with a population of over 350, 000, to be covered; assessing young infants at home and arranging timely transport of sick young infants to study hospitals for physician confirmation of illness; and specimen collection and treatment. A large workforce is deployed in a 3-tier system in the field, while clinical, microbiology, laboratory and data management teams collaborate dynamically. Mobile phones with text message capability, integration with the Odisha State government's health system, involvement of local communities and strict monitoring at different levels have been critical in addressing these challenges. Conclusion: This article describes the challenges and modalities adopted to collect complex and accurate data on etiology, timing of disease and associated factors for community-acquired neonatal infections. Attention to local culture and customs, training and employing community level workers and supervisors, involving existing government machinery, using technology (cell phones), and uninterrupted systematic monitoring are critical for implementing such complex protocols that aim to collect population-based data to drive policy.